Memories, Crossings, and Station Stops: Displaced Pasts into Present Teaching of Language and Art - Morawski, Cynthia Marlene; Cloutier, Geneviève (Journal of the Canadian Association for Curriculum Studies, 2016)
Whether photographed from the missing pages of a summer day, or surrounded by the light of spectral clouds passing through a whisper, stories that provoke connections between person and place can be both powerful and inspiring in the recurring creation of teaching narratives. What happens when we, a professor and a doctoral student, come together to critically inquire into the displaced pasts of our present selves for future teachers of language and art? Which locations will we select? Where will our dialogue take us? We respond in a composition of poetry, prose, and image.